Antenatal care and breastfeeding practices in Sub-Saharan Africa: an analysis of demographic and health surveys - Bolanle Olapeju; Michael Bride; Mariam Wamala; Deborah Atobrah; Elizabeth H. Lee; Zoé M. Hendrickson (BMC Pregnancy and Childbirth)
Abstract Background The World Health Organization (WHO) recommends immediate breastfeeding (within the first hour after birth) and exclusive breastfeeding (for the first six months of life), particularly in low-resource settings such as sub-Saharan Africa. In 2016, WHO updated its antenatal care (ANC) guidelines, recommending at least eight (8+) ANC contacts during pregnancy to improve maternal and child health outcomes. This study investigates i) trends in breastfeeding practices across sub-Saharan Africa following the rollout of the revised WHO 2016 ANC policy and ii) the relationship between ANC uptake and exclusive or early breastfeeding. Methods We performed a secondary analysis of Demographic and Health Survey data from 19 countries, from 2018-2023. Key variables included exclusive breastfeeding, early initiation of breastfeeding (within one hour of birth), and the number of ANC contacts (categorized into 0-3, 4-7, and 8 + visits) among mothers with a live birth in the six months preceding the survey. Results Exclusive breastfeeding rates ranged from 19% in Gabon to 81% in Rwanda (median = 53%), while early initiation of breastfeeding ranged from 32% in Senegal to 85% in Rwanda (median = 60%). The percentage of women with 8 + ANC contacts ranged from 0.3% in Rwanda to 39% in Ghana (median = 4%). Women with 8 + ANC contacts did not show increased odds of early initiation (aOR: 0.94; 95% CI: 0.84, 1.05) or exclusive breastfeeding (aOR: 0.85; 95% CI: 0.76, 0.94) compared to women with 4-7 contacts. Discussion These findings reveal low rates of 8 + ANC contacts against a backdrop of suboptimal breastfeeding practices across sub-Saharan Africa. Furthermore, the results suggest limited additional benefits of 8 + ANC contacts over 4-7 contacts in promoting immediate and exclusive breastfeeding, as recommended by the WHO 2016 ANC policy. Urgent efforts are needed to promote ANC uptake and improve the quality of ANC contacts through behavior change interventions and complementary health service delivery. Sub-national, national, and global stakeholders should prioritize these interventions.